Alain Canard (2005): Catalogue of spider species from Europe and the Mediterranean basin. Parts I & II - Helsdingen, Peter van (Arachnologische Mitteilungen, 2007)

(untitled)
book review: Alain Canard (2005): Catalogue of spider species from Europe and the Mediterranean basin. Parts I & II.